Thoracoscopic excision of pediatric thymic cysts - Fabiano Nino; Giulia Fusi; Edoardo Bindi; Michele Ilari; Carmine Noviello; Giovanni Torino; Giovanni Cobellis (Elsevier, 2021)
Introduction: Thymic cysts are rare lesions that may be congenital or acquired, and should be considered in the differential diagnosis in pediatric neck-thoracic masses. They are most of the time asymptomatic, presenting as slow-growing, painless masses. Evolution is generally benign, however surgical excision is considered the first choice for treatment, and could be performed via open technique (sternotomy) or with minimally invasive technique (thoracoscopy). Both techniques are safe and present little risk of postoperative recurrence, although thoracoscopic approach presents some advantages in terms of reduced postoperative pain, reduced surgical time and reduced length of hospital stay. Case series: A retrospective review of medical records of all patients admitted to our center in the last 5 years for surgical treatment for thymic cysts was performed. We recorded and evaluated clinical data, surgical data and follow-up data. In the reference period 3 patients were admitted with thymic cysts at our center. They all underwent complete minimally invasive excision by video assisted thoracoscopic surgery (VATS). Histopathological analysis revealed in 2 cases multilocular thymic cysts and in 1 case cystic thymic teratoma. Mean follow-up was 21 months. In the follow-up period any patients developed sympthoms, complications or relapses. Conclusion: According to our experience, thoracoscopic approach to thymic cyst is feasible, safe and allows a radical treatment of lesion offering excellent cosmetic results.